En route from artificial to natural: Evaluation of inhibitors of mannose-specific adhesion of E. coli under flow - Möckl, Leonhard; Fessele, Claudia; Despras, Guillaume; Bräuchle, Christoph; Lindhorst, Thisbe K. (Biochimica et Biophysica Acta - General Subjects, 2016)
We investigated the properties of six Escherichia coli adhesion inhibitors under static and under flow conditions. On mannan-covered model substrates and under static conditions, all inhibitors were able to almost completely abolish lectin-mediated E. coli adhesion. On a monolayer of living human microvascular endothelial cells (HMEC-1), the inhibitors reduced adhesion under static conditions as well, but a large fraction of bacteria still managed to adhere even at highest inhibitor concentrations. In contrast, under flow conditions E. coli did not exhibit any adhesion to HMEC-1 not even at inhibitor concentrations where significant adhesion was detected under static conditions. This indicates that the presence of shear stress strongly affects inhibitor properties and must be taken into account when evaluating the potency of bacterial adhesion inhibitors.
CRIS-Team Scopus Importer:2024-09-09
Keywords: Antiadhesion therapy; Bacterial adhesion; Carbohydrate recognition; Flow conditions; Shear stress